Comparison of atrial fibrillation ablation efficacy using remote magnetic navigation vs. manual navigation with contact-force control - Jez, Jiri; Jadczyk, Tomasz; Lehar, Frantisek; Pesl, Martin; Kulik, Tomas; Belaskova, Silvie; Soucek, Filip; Caluori, Guido; Wojakowski, Wojciech; Starek, Zdenek (Biomedical papers, 2020)
Aims: This study aims to compare procedural parameters and clinical efficacy of remote magnetic navigation (RMN) vs. manual navigation (MAN) approach for radiofrequency ablation (RFA) in patients with atrial fibrillation (AF). Methods: 146 patients with AF were enrolled in the study. In the RMN group (n=57), patients were treated with the CARTO(R) 3 in combination with the Niobe ES system. In the MAN group (n=89), ablation was performed with the EnSite Velocity and TactiCath™ Quartz catheter with direct contact force measurement. Procedural time, ablation time, fluoroscopy time, radiation dose and ablation counts were measured and compared between the groups. Recurrence of AF was evaluated after 6 months of follow-up. Results: Mean procedure times (236.87 extpm64.31 vs. 147.22 extpm45.19 min, P<0.05), counts of RF applications (74.30 extpm24.77 vs. 49.15 extpm20.33, P<0.05) and total RFA times (4323.39 extpm1426.69 vs. 2780.53 extpm1157.85 s, P<0.05) were all significantly higher in the RMN than in the MAN group, respectively. In the same order, mean X-ray dose (9722.6 extpm7507.4 vs. 8087.9 extpm6051.5 mGy/cm2, P=0.12) and mean total X-ray exposure time (8.07 extpm4.20 vs. 9.54 extpm5.47 min, P=0.08) were not statistically different. At 6-month follow-up, freedom from AF was similar in RMN and MAN group for paroxysmal (60.8% and 73%, respectively, P=0.42) and persistent AF (69.6% and 75.0%, respectively, P=0.77). Conclusions: Due to the fact that mid-term clinical outcomes showed no significant differences in AF recurrences between groups and manual ablation strategy provided more favorable results regarding acute procedural parameters, we can conclude that the remote magnetic navigation is not superior to the manual approach.
Keywords: atrial fibrillation; radiofrequency ablation; electro-anatomical mapping; remote magnetic navigation; contact-force technology